Fibronectin chorused cohesion between endothelial progenitor cells and mesenchymal stem cells of mouse bone marrow - Zhang, H. W; Chen, X. L; Lin, Z. Y; Xia, J; Hou, J. X; Zhou, D; Xi, Y; Zhang, M; Guo, J; Feng, W; Peng, X. Y; Wu, X. W (Cellular and Molecular Biology, 2015)
Endothelial progenitor cells (EPCs) could function as niche cells to promote self-renewal of mesenchymal stem cells (MSCs) in the mouse bone marrow. Cohesion was the basis of the two cells to display their biological functions to each other. In this study, we investigated the mechanism of cohesion between MSCs and EPCs. And demonstrated that fibronectin (FN) in EPCs activated the integrin Î±5Î²1 of MSCs and further mediated cell–cell cohesion. Integrin Î±5Î²1 and its FN ligand played critical roles not only in single-cell line adhesion, but also in adhesion between stem and niche cells. This novel finding is important to understand the cross-talk between MSCs and their niche cells.